The Influence of Managerial Ability of School Principals and The Climate of School Organizations on Teacher Performance During The Covid-19 Pandemic - E, Khuluqo I; M, Tenkahary C (Journal of Education Technology, 2021)
The role of the school principal is an important factor in optimizing teacher performance during the Covid-19 pandemic. In addition, the conducive school organization's climate is able to provide solutions to a variety of teacher performance problems that arise during the Covid-19 Pandemic. This study aims to examine the influence of Managerial Ability of School Principals and Climate School Organizations on Teacher Performance during the Covid-19 Pandemic in private Madrasah Tsanawiyah in Parung Subdistrict, Bogor Regency.Â  The research method used is quantitative method by taking a sample of 126 teachers from a population of 184 teachers. Before the study was conducted trials on 33 teachers outside the sample. The results showed that the principal school's managerial ability influenced the teacher's performance indicated by a Fcount score of 92,102 (p < 0.05) and had a strong tightness based on a correlation coefficient value of 0.653. Subsequently, the climate of the school organization influenced teacher performance indicated by a Fcount score of 126.784 (p < 0.05) and had a strong tightness based on a correlation Â coefficient of 0.711. In addition, the managerial ability of the school principal and the climate of the school organization simultaneously affect the performance of teachers based on the Fcount score of 75,497 (p < 0.05) and have a strong tightness based on an R score of 0.742.